2020
DOI: 10.1111/and.13774
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted laparoscopic artery‐sparing varicocelectomy using indocyanine green fluorescence angiography: Initial experience

Abstract: We reported our initial experience of robotic‐assisted laparoscopic artery‐sparing varicocelectomy using indocyanine green (ICG) fluorescence angiography in treatment of varicocele. A total of 45 varicocelectomies in 27 patients were performed. The mean operation time was 49.1 ± 8.5 min for unilateral and 65.6 ± 8.3 min for bilateral repair. 47.2 s after ICG injection, testicular artery (TA) was visualised. After an interval of 31.3 s, fluorescent veins were identified. Of all the 45 spermatic cords, 68.9% had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A varicocele represents an abnormal enlargement of the veins within the pampiniform plexus and has been recognized as one of the most frequent causes of infertility in men, with an incidence in the pediatric population of 10-15% [1]. Around 40% of adult males with this abnormality are infertile [1][2][3]. The usual modality of treatment, with a very high success rate, is surgical varicocelectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A varicocele represents an abnormal enlargement of the veins within the pampiniform plexus and has been recognized as one of the most frequent causes of infertility in men, with an incidence in the pediatric population of 10-15% [1]. Around 40% of adult males with this abnormality are infertile [1][2][3]. The usual modality of treatment, with a very high success rate, is surgical varicocelectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The usual modality of treatment, with a very high success rate, is surgical varicocelectomy. Today, several surgical approaches for successful varicocele treatment are available, including open inguinal, subinguinal microscopic laparoscopic, and robotic-assisted laparoscopic ligation [1][2][3][4]. Due to the benefits of minimally invasive surgery, laparoscopic varicocelectomy has been popularized and has gained growing acceptance among pediatric surgeons [4].…”
Section: Introductionmentioning
confidence: 99%
“…The da Vinci surgical system is the only commercially available robotic platform, widely used for several types of surgical procedures ( 38 ). Recently some studies showed robotic use in microsurgical procedures for male infertility included varicocele treatment ( 39 , 40 ). Subinguinal microscopic varicocelectomy showed superior outcomes compared with other techniques ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Robotic varicocelectomy shows several limitations: first, the cost of robotic surgery is much higher than other approaches. Second, external spermatic perforators/gubernacular veins could not be handled under a robotic laparoscopic approach ( 39 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…ear-infrared fluorescence (NIRF) imaging technology using indocyanine green (ICG) as the fluorescent agent has been shown to be beneficial in numerous robotic procedures. [1][2][3][4][5][6][7] The current generation of robots, such as da Vinci Xi (Intuitive Surgical, Sunnyvale, CA), is equipped with a software for NIRF detection, named FireflyR (Novadaq Technologies, Mississauga, Ontario, Canada), directly controlled by the console surgeon. 1 The vascular anatomy can be visualized within seconds after the intravenous injection of ICG.…”
mentioning
confidence: 99%